The new Cambridge history of the English language: Volume II: Documentation, sources of data and modelling - Kytö, Merja; Smitterberg, Erik; Hickey, Raymond (Cambridge University Press, 2025)
This volume considers the various kinds of text which document the history of the English language. It looks closely at vernacular speech in writing and the broader context of orality along with issues of literacy and manuscripts. The value of text corpora in the collection and analysis of historical data is demonstrated in a number of chapters. A special focus of the volume is seen in the chapters on genre and medium in the textual record. Various types of evidence are considered, for instance, journalistic work, medical writings, historiography, grammatical treatises and ego documents, especially emigrant letters. A dedicated section examines the theories, models and methods which have been applied to the textual record of historical English, including generative and functionalist approaches as well as grammaticalisation and construction grammar. In addition, a group of chapters consider the English language as found in Beowulf and the writings of Chaucer and Shakespeare.